1978
DOI: 10.21273/hortsci.13.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Relative Humidity Effects on the Postharvest Life of Fruits and Vegetables1

Abstract: We all pay lip service to the concept that fruits and vegetables are alive. Nevertheless, very little attention is paid to what must be a major trauma for most of them, being suddenly cut off at harvest from the water supply that has hitherto sustained them. While on the plant, the organs that we call fruits and vegetables participated in a dynamic traffic in water due to transpiration and to withdrawal of water by the plant in times of stress (40). At harvest, this suddenly ceases and for water, as well as ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One of the most significant unfavorable signs in fruit preservation is water loss, which affects the fruit's quality, causes shrinkage, and makes marketing the preserved fruit more challenging ( Grierson and Wardowski, 1978 , Kawada and Albrigo, 1979 ). The obtained results may be attributable to the post-harvest handling technique, wax coating, wich showed that edible films and coatings changed the environments and reduced weight loss during transport and storage by limiting the permeability and gaseous exchange ( Cuq et al, 1995a , Cuq et al, 1995b ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant unfavorable signs in fruit preservation is water loss, which affects the fruit's quality, causes shrinkage, and makes marketing the preserved fruit more challenging ( Grierson and Wardowski, 1978 , Kawada and Albrigo, 1979 ). The obtained results may be attributable to the post-harvest handling technique, wax coating, wich showed that edible films and coatings changed the environments and reduced weight loss during transport and storage by limiting the permeability and gaseous exchange ( Cuq et al, 1995a , Cuq et al, 1995b ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors that negatively affect fruit quality is water loss, which reduces its commercial life after harvest [77]. For orange fruits, a 2.5% weight loss causes a contraction to begin, and a 5% loss of its original weight makes it no longer marketable [78]. Murcott mandarin fruit weight loss increased progressively in all treatments with the increasing storage period, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%